Pengaruh Pembelajaran Berbantuan Geogebra terhadap Kemampuan Penalaran Matematis Siswa : Meta Analisis - Dhiya Ulhanan; Sashi Kirana Zahrani Putri; Syamsa Nura; Rena Revita (Lembaga Pengembangan Kinerja Dosen, 2025)
Mathematical reasoning skills are an important aspect of mathematics learning that supports students in understanding concepts deeply and logically. With the development of technology, the use of interactive learning media such as Geogebra has become a promising alternative to improve the quality of learning. This study aims to analyze the effect of Geogebra-assisted learning on students' mathematical reasoning skills through a meta-analysis approach. The method used is a Systematic Literature Review (SLR) guided by the PRISMA guidelines, covering publications from 2015 to 2025 that meet specific inclusion criteria. The analysis of seven research articles revealed that six of them showed a large to very large effect on improving mathematical reasoning skills, while one article showed a small effect. These findings reinforce the conclusion that Geogebra is generally effective in supporting the development of students' mathematical reasoning skills and is worthy of being part of mathematics learning strategies in the digital age.